A novel phenylcyclohex‐1‐enecarbothioamide derivative inhibits CXCL8‐mediated chemotaxis through selective regulation of CXCR2‐mediated signalling. (March 2014) - Ha, Helen; Bensman, Tim; Ho, Henry; Beringer, Paul M; Neamati, Nouri
<x xml:space="preserve">Abstract</x> Background and Purpose Since the CXC chemokine receptor CXCR2 and its cognate ligand CXCL8 (IL‐8) critically regulate neutrophil trafficking during inflammation, they have been implicated in a number of inflammatory lung diseases. Several CXCR2 antagonists have been described and the blockade of CXCR2 has shown promise in pre‐clinical disease models and early clinical trials. However, given its potential, there are fewer distinct classes of antagonists of CXCR2 than of other clinically relevant molecular targets. Thus, we sought to identify additional classes of compounds that alter CXCR2 function. Experimental Approach We used the CXCR2 TangoTM assay to screen an in‐house library of highly diverse chemical compounds. CX4338 [2‐(benzylamino)‐4, 4‐dimethyl‐6‐oxo‐N‐phenylcyclohex‐1‐enecarbothioamide] was identified from our screen and additional studies to characterize the compound were performed. Receptor internalization and second‐messenger assays were used to assess the effects of CX4338 on CXCR2‐mediated signalling. Wound healing, transwell cell migration and LPS‐induced lung inflammation in mice were used to determine the in vitro and in vivo effects of CX4338. Key Results CX4338 selectively inhibited CXCR2‐mediated recruitment of β‐arrestin‐2 and receptor internalization, while enhancing CXCR2‐mediated MAPK activation. Additionally, CX4338 inhibited CXCL8‐induced chemotaxis in CXCR2‐overexpressing cells and human neutrophils. In vivo, CX4338 significantly reduced neutrophils in bronchoalveolar lavage induced by LPS in mice. Conclusions and Implications A novel compound CX4338 inhibited CXCR2‐mediated cell migration with a mechanism of action not previously reported. Also, selective inhibition of CXCR2‐mediated β‐arrestin‐2 activation is sufficient to inhibit CXCL8‐mediated chemotaxis.